Search for Optimal CEO Compensation: Theory and Empirical Evidence - CAO, Melanie (Institutional Knowledge at Singapore Management University, 2008)
We integrate an agency model with dynamic search equilibrium to study three important issues concerning executive compensation. We show that 1) the equilibrium pay-to-performance sensitivity depends positively on a firm’s specific risk, and negatively on its systematic risk, which offers a plausible explanation for the inconclusive empirical relationship between the pay-to-performance sensitivity and a firm’s total risk; 2) a growing economy simultaneously induces the growth in executive compensation and firm size; 3) the faster growth of executive compensation relative to the growth of firm size in the past decade is mostly due to the increase in firms’ specific risks.